Over-expression by degradation rescue of RTKs via cancer-secreted autocrine growth factors: a Phospho-degron-driven actionable layer of post-translational regulation? - Scalia, Pierluigi; Williams, Stephen J. (Frontiers in Oncology, 2023)
Recently published work provide the first known evidence of a malignancy-associated regulatory mechanism, functionally connecting a phospho-regulated degron domain embedded in a receptor tyrosine kinase (RTK), with its ectopic expression in cancer, conditional to a specific autocrine growth factor signal. Mechanistically, the growth factor-triggered phosphorylation inhibits the degron domain present in the regulated RTK, blocking access to a specific degradation complex. This ultimately rescues the RTK from rapid ubiquitin-proteasome-system-mediated degradation and, most importantly, causes its cellular overexpression. This mechanism, which has been here assigned the new functional name "Over-Expression by Degradation Rescue" (OEDR), provides an additional layer and potentially preferential tool for the control of RTKs expression in cancer, in addition to other mechanisms acting at the transcriptional and messenger transcript stabilization levels. We propose this newly defined phosphorylation/ubiquitination switch-dependent signal to bear wider unexploited relevance in cell biology and human pathophysiology. The recently identified mechanism underlying an OEDR-regulated RTK is discussed herein in the context of physiological endocrine circuits and cancer.